Individual Differences in the Acceptance and Adoption of AI-enabled Autonomous Systems. (September 2022) - Weger, Kristin; Easley, Tiffanie; Branham, Nathaniel; Tenhundfeld, Nathan; Mesmer, Bryan
With the deployment of AI-enabled autonomous systems in various fields of application, it is critical to understand the factors affecting the acceptance and in turn the adoption of such technology. While previous research has established that individual differences have an impact on the acceptance and adoption of technology, little research has examined the extent and specificity of those individual differences. The current research attempts to address this gap in the literature by examining individual differences concerning the willingness to accept and adopt general technology versus specific AI-enabled autonomous systems. Our findings reveal several significant results between an individual's personality traits of Openness, Emotionality, and Honesty-Humility, as well as age, gender, and career field with an individual's level of acceptance and adoption of general versus specific AI-enabled AS technology. Our findings call for future research to further explore these individual differences in detail and to validate current technology models.